Early cryoprecipitate transfusion versus standard care in severe postpartum haemorrhage: a pilot cluster‐randomised trial. (20th October 2021) - Green, L.; Daru, J.; Gonzalez Carreras, F. J.; Lanz, D.; Pardo, M. C.; Pérez, T.; Philip, S.; Tanqueray, T.; Khan, K. S.
Summary: There is a lack of evidence evaluating cryoprecipitate transfusion in severe postpartum haemorrhage. We performed a pilot cluster‐randomised controlled trial to evaluate the feasibility of a trial on early cryoprecipitate delivery in severe postpartum haemorrhage. Pregnant women (>24 weeks gestation), actively bleeding within 24 h of delivery and who required at least one unit of red blood cells were eligible. Women declining transfusion in advance or with inherited clotting deficiencies were not eligible. Four UK hospitals were randomly allocated to deliver either the intervention (administration of two pools of cryoprecipitate within 90 min of first red blood cell unit requested plus standard care), or the control group treatment (standard care, where cryoprecipitate is administered later or not at all). The primary outcome was the proportion of women who received early cryoprecipitate (intervention) vs. standard care (control). Secondary outcomes included consent rates, acceptability of the intervention, safety outcomes and preliminary clinical outcome data to inform a definitive trial. Between March 2019 and January 2020, 199 participants were recruited; 19 refused consent, leaving 180 for analysis (110 in the intervention and 70 in the control group). Adherence to assigned treatment was 32% (95%CI 23–41%) in the intervention group vs. 81% (95%CI 70–90%) in the control group. The proportion of women receiving cryoprecipitate at any time‐point was higher in the intervention (60%) vs. control (31%) groups; the former had fewer red blood cell transfusions at 24 h (mean difference −0.6 units, 95%CI −1.2 to 0); overall surgical procedures (odds ratio 0.6, 95%CI 0.3–1.1); and intensive care admissions (odds ratio 0.4, 95%CI 0.1–1.1). There was no increase in serious adverse or thrombotic events in the intervention group. Staff interviews showed that lack of awareness and uncertainty about study responsibilities contributed to lower adherence in the intervention group. We conclude that a full‐scale trial may be feasible, provided that protocol revisions are put in place to establish clear lines of communication for ordering early cryoprecipitate in order to improve adherence. Preliminary clinical outcomes associated with cryoprecipitate administration are encouraging and merit further investigation.